Analisis Jaringan Sosial Keagamaan Nahdlatul Ulama dalam Pengelolaan Konflik Antarumat Beragama di Indonesia - Ahmad Yani; Ahmad Ahmad; Ramli Ramli (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Indonesia faces interfaith conflict challenges amid high cultural diversity, prompting Nahdlatul Ulama (NU) to leverage its religious social network for mediation and dialogue. This study formulates issues on the structure, effectiveness, and optimization of NU’s network in conflict resolution through analysis of 10 key actors and 21 collaborative ties. A qualitative method with Social Network Analysis (SNA) approach using Gephi processes node data (influence score 0.65–0.95) and edge data (weight 3.9–9.4) from 2023. Results reveal PBNU as the coordination hub with density 0.42 and 90% positive outcomes such as local peace and mutual respect, though minority ties remain weak. Discussion analysis confirms network resilience against radicalism. In conclusion, NU’s network effectively sustains national harmony; recommendations include strengthening minority inclusion and real-time SNA dashboard.